Porous magnesia-alumina composite nanoparticle for biodiesel production. (1st February 2021) - Chen, Yu-Shen; Yang, Che-Ming; Nguyen Hoang, Thanh Truc; Tsai, De-Hao
Graphical abstract: Highlights: Aerosol-based synthesis of Mg-Al-O composite nanocatalyst for biodiesel production. Surface area of MgO nanocatalyst increased via hybridization with Al2 O3 . A maximum of 3.4× in yield by using Mg-Al-O composite nanocatalyst. Strong basic site and catalytic activity increased by hybridization MgO with Al2 O3 . Sufficient high operation stability and chemical stability in cyclic test. Abstract: A facile, aerosol-based controlled synthesis of porous Mg-Al-O composite nanoparticle is demonstrated for developing solid base catalysts with high performance for transesterification of soybean oil to biodiesel. Pore size, crystallite size and chemical composition of the Mg-Al-O composite nanoparticle are tunable by design. A significantly higher surface area (by 1.8 times) and a smaller pore size (i.e., decreased by 20%) of the Mg-Al-O composite particle achieved by using the aerosol-based synthesis than the conventional method. Hybridization with Al2 O3 remarkably increased surface area of the MgO particle by decreasing pore size using homogenous Al precursor or increasing pore volume via choosing heterogeneous Al precursor. The fatty acid methyl esters (FAME) yield catalyzed by Mg-Al-O composite particle was significantly higher in comparison to the results without catalysts (i.e., a maximum of 3.4×). The FAME yield was proportional to methanol-to-oil molar ratio, and the highest yield was identified at Mg/Al = 4, in accordance to the highest number of strong basic site quantified via a CO2 -based temperature-programmed desorption study. Operation stability (i.e., FAME yield declined by <4%) and chemical stability (i.e., mass leaching <0.06% of total catalyst mass) were sufficiently high for the synthesized porous Mg-Al-O composite nanoparticle based on the 3-cycle test. The work establishes a prototype study of developing porous Mg-Al-O composite nanostructure by applying a gas-phase evaporation-induced self-assembly to achieve high activity and operation stability. The study also shows promise to further enhance strong basicity and corresponding catalytic activity through mechanistic understanding of the designed composite nanocatalyst.